Bahaya Radikalisme terhadap NKRI - Nur Khamid (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
An ideology, is needed by a nation to bind the people to live together in the shade of one ideology. Likewise in Indonesia that the founding fathers already set ideology of Pancasila as the nation of Indonesia, it is automatically Pancasila becomes the nation’s ideology that must be obeyed and followed by the whole nations. Pancasila is an ideology with the principle of “Bhinneka Tunggal Ika” which teaches us to always live with a sense of tolerance. Due to the presence of many religious, ethnic, racial and flow, but the essence is one also, the one nation, the nation of Indonesia. Lately emerged a new ideology in Indonesia that is very disturbing society, namely the ideology of radical Islam. An exclusive ideology that always puts the violence in the realization of its goals. Dogmas contained in the teachings of Islam interpretednarrowly and misused to legitimize any radical action. The ideology of radical Islam is very much influenced by the ideology of ISIS or the Islamic State in Iraq and Syria, which is a group of militant jihad idiology, that is being developed all over the world through websites, books, education in schools, campuses, lecture , social networks like face book, you tube, twitter etc.